EFEKTIFITAS PENGGUNAAN MEDIA ELMANTAB TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM - Khasanah Khasanah; Deden Marjuki; Nursanita Nasution (Akademika, 2021)
This study aims to describe the application and effectiveness of the use of Elmantab media in Natural Sciences subjects in grade IV of Al Hamid Integrated Islamic Madrasah. Elmantab media is an application developed independently by the Mantab Al Hamid Foundation, which is located at Jalan Cilangkap Baru, Cilangkap Kelurahan, Cipayung District, East Jakarta City. This online-based learning application is a paid application to the relevant provider. This type of research is qualitative. The problems in this study are clearly described in the results of the research obtained based on the facts obtained in the field. The data collection techniques used consisted of observation, interview (interview), questionnaire and documentation. The research subjects were the school principal, science teacher at grade IV and 106 grade IV students at the Al Hamid Integrated Madrasah Ibtidaiyah in the 2020/2021 school year. Data analysis using triangulation techniques methods and data sources. This study also uses Milles-Duberman analysis techniques through the stages of reduction, exposure to data and drawing conclusions. The results showed that the use of Elmantab was declared effective in the distance learning process. The learning outcomes of students in the Natural Sciences subject get excellent grades. Evidenced by documentation and the results of interviews with class IV science teachers. The average score obtained was 87.36 for the cognitive aspects and the average score was 86.26 for the psychomotor aspects. As for the percentage of student learning completeness both cognitive and psychomotor 92.07% and 97.02%. The percentage of student learning completeness in both cognitive and psychomotor aspects was 92.07% and 97.02%.